Factors of mastering of terms of information and communication technologies and difficulties of application of terms in practice (Texas Journal of Philology, Culture and History, 2021)
ICT terms are a relatively new field for the Uzbek language, which has entered the Uzbek lexicon through Russian and directly through English. Therefore, most ICT terms have features specific to English lexicon. The article describes in detail the factors of language acquisition related to language, views within the language system, their causes and conditions of acquisition, lexical innovations, their causes, difficulties in the process of acquisition.